Exploring Mathematical Thinking Obstacles through the Lens of Self-Efficacy - Galuh Ajeng Nurazizah; Dian Septi Nur Afifah; Maylita Hasyim; Diesty Hayuhantika; Silfia Hayuningrat (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2026)
This study investigates elementary students’ mathematical thinking obstacles through the lens of self-efficacy in mathematics learning. Adopting a qualitative descriptive design, data were gathered through non-participant classroom observations, open-ended interviews, a Likert-scale self-efficacy questionnaire, and document analysis. Participants consisted of one fifth-grade teacher and six fifth-grade students selected purposively. Students’ self-efficacy levels were categorized as high, moderate, or low through triangulation of questionnaire scores, classroom observations, and interview findings to ensure consistency between students’ perceived beliefs and their actual learning behaviors. Data analysis followed the stages of data reduction, data display, and conclusion drawing. The findings indicate that students with high self-efficacy demonstrated persistence, confidence, learning autonomy, and effective emotional regulation when solving mathematical problems. Students with moderate self-efficacy tended to rely on previous learning experiences and familiar procedures, whereas students with low self-efficacy exhibited limited confidence, hesitation, and a tendency to disengage from challenging tasks. Mathematical thinking obstacles were identified as instrumental ontogenic, conceptual ontogenic, didactical, and epistemological. The ontogenic category was operationally divided into instrumental and conceptual dimensions to distinguish procedural difficulties from conceptual misunderstandings, enabling a more detailed analysis of students’ cognitive obstacles. Among these categories, didactical obstacles emerged as the most dominant, particularly students’ reliance on teacher-provided examples and difficulties in independently initiating problem-solving processes. Overall, the findings suggest an observed tendency that students with higher self-efficacy experience fewer and less complex mathematical thinking obstacles. The study highlights the importance of integrating self-efficacy-enhancing strategies into mathematics instruction to foster more autonomous, resilient, and effective mathematical thinking among elementary students.